Zinc Binding to NAP-Type Neuroprotective Peptides: Nuclear Magnetic Resonance Studies and Molecular Modeling - Ancuta-Veronica Lupaescu; Cosmin Stefan Mocanu; Gabi Drochioiu; Catalina-Ionica Ciobanu (MDPI AG, 2021)
Aggregation of amyloid-β peptides (Aβ) is a hallmark of Alzheimer's disease (AD), which is affecting an increasing number of people. Hence, there is an urgent need to develop new pharmaceutical treatments which could be used to prevent the AD symptomatology. Activity-dependent neuroprotective protein (ADNP) was found to be deficient in AD, whereas NAP, an 8-amino-acid peptide (1NAPVSIPQ8) derived from ADNP, was shown to enhance cognitive function. The higher tendency of zinc ion to induce Aβ aggregation and formation of amorphous aggregates is also well-known in the scientific literature. Although zinc binding to Aβ peptides was extensively investigated, there is a shortage of knowledge regarding the relationship between NAP peptide and zinc ions. Therefore, here, we investigated the binding of zinc ions to the native NAP peptide and its analog obtained by replacing the serine residue in the NAP sequence with tyrosine (1NAPVYIPQ8) at various molar ratios and pH values by mass spectrometry (MS) and nuclear magnetic resonancespectroscopy (NMR). Matrix-assisted laser desorption/ionization time-of-flight (MALDI ToF) mass spectrometry confirmed the binding of zinc ions to NAP peptides, while the chemical shift of Asp1, observed in 1H-NMR spectra, provided direct evidence for the coordinating role of zinc in the N-terminal region. In addition, molecular modeling has also contributed largely to our understanding of Zn binding to NAP peptides.